The impact of biomechanical analysis on sports performance of taekwondo athletes: a scoping review - Armando Monterrosa Quintero; Oscar Alfredo Montenegro Arjona; Felipe Poblete Valderrama (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Background: biomechanical analysis plays a fundamental role in enhancing athletic performance and preventing injuries, as it encompasses both qualitative and quantitative methods to evaluate techniques and tactics in taekwondo.